Cultural Identity in Bahamian Art Music: The Expression of Four Bahamian Composers - Wright, Carlton Leroy; Gangelhoff, Christine (International Journal of Bahamian Studies, 2013)
This article is a transcription of the presentations of the participants of the first session of the International Symposium on Composers of African and Afro-Caribbean Descent held at the College of The Bahamas in February 2013. Edward Bethel moderated the session, which included guest artists Cleophas Adderley, Audrey Dean-Wright, Christian Justilien, and K. Quincy Parker. These four prominent Bahamian composers discussed their pieces, focusing on their compositional style and how/if cultural identity is a strong component of their works. Featured compositions contain hyperlinks to audio/video-recorded examples.